2018
DOI: 10.1016/j.tig.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of CRTCs in Aging and Age-Related Disease Risk

Abstract: Advances in public health in the last century have seen a sharp increase in human life expectancy. With these changes have come increased incidence of age-related pathologies and health burdens in the elderly. Patient age is the biggest risk factor for multiple chronic conditions that often occur simultaneously within one individual. An alternative to disease centric therapeutic approaches is that of 'geroscience', which aims to define molecular mechanisms that link age to overall disease risk. One such mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 79 publications
(119 reference statements)
1
8
0
Order By: Relevance
“…In lymphocytes, MYC binds thousands of genes and acts to broadly amplify the expression of bound genes rather than functioning as an on/off switch (Nie, Hu et al, 2012). By an imperfect analogy, we identified CRTC2 bound to more than 4,500 genes in naïve WT mouse B cells by ChIP-seq (unpublished observation), many of which were not predicted as CREB target genes, in agreement with prior results that showed CRTC proteins interact with additional bZIP family transcription factors (Escoubas, Silva-Garcia et al, 2017). In TG PCs, large changes in expression of specific genes were few, but small changes in expression did occur for numerous genes between TG and WT PCs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In lymphocytes, MYC binds thousands of genes and acts to broadly amplify the expression of bound genes rather than functioning as an on/off switch (Nie, Hu et al, 2012). By an imperfect analogy, we identified CRTC2 bound to more than 4,500 genes in naïve WT mouse B cells by ChIP-seq (unpublished observation), many of which were not predicted as CREB target genes, in agreement with prior results that showed CRTC proteins interact with additional bZIP family transcription factors (Escoubas, Silva-Garcia et al, 2017). In TG PCs, large changes in expression of specific genes were few, but small changes in expression did occur for numerous genes between TG and WT PCs.…”
Section: Discussionsupporting
confidence: 88%
“…Patients harboring mutations in ATM exhibit defective antibody responses (Staples, McDermott et al, 2008) and mouse B cells lacking LKB1 fail to generate ASCs in vitro (Walsh, Waters et al, 2015). Identifying direct CRTC2-bound genes may help elucidate potential stage-specific targets, although this may prove challenging as CRTCs bind and co-activate multiple bZIP transcription factors in addition to CREB (Escoubas et al, 2017). In addition, CRTC family member proteins may have redundant functions, making stage-specific CRTC2 deletion studies difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…CRTC/CRTC-1 acts downstream of SIK2/AAK-2 to regulate neuroprotection in nematode excitotoxicity AAK-2 has been previously shown to phosphorylate CRTC-1, thus determining its cytoplasmic vs. nuclear distribution (Altarejos and Montminy 2011;Mair et al 2011;Sasaki et al 2011;Burkewitz et al 2014Burkewitz et al , 2015Escoubas et al 2017). However, AAK-2 has also been shown to regulate the activity of FoxO/DAF-16 to modulate levels of neurodegeneration (Greer et al 2007;Tullet et al 2014;Vazquez-Manrique et al 2016).…”
Section: The Non-canonical Mediators Of Creb/crh-1 Activation Are Cenmentioning
confidence: 99%
“…In addition, several other studies have indicated rapid enhancement of BDNF expression and synaptic plasticity in the special regions of brain, which is responsible for the antidepressant effect (Udina et al., 2016). Also, the transcription activator CREB has also been shown to be central in response to many signal cascades activated through growth factor, synaptic activity, and other cellular stimuli related to neuronal plasticity (Escoubas et al., 2017; H. Liu et al., 2015; Ning et al., 2019). Moreover, an equally important coactivator CRTC, also known as transducer of regulated CREB (TORC), has been recognized to play an important role in influencing CREB function (Heinrich et al., 2013).…”
Section: Introductionmentioning
confidence: 99%